Th17 and Th1 Lymphocytes in Oligoarticular Juvenile Idiopathic Arthritis - Maggi, Laura (Front Immunol, 2019)
In the last years much attention has focused on the Th17 and Th1 phenotypes and on their pathogenic role in juvenile idiopathic arthritis, investigating how the cytokines produced by T helper cells act on resident cells on the synovia and which signal transduction pathways regulate Th17 cells proliferation and plasticity. In this context, an important milestone was represented by the identification of the non-classic Th1 phenotype, developed from the shift of Th17 cells. The cytokine TNF-α, beyond its well-known proinflammatory activity is involved in this process and this is one of the reasons why the TNF-α inhibitors are widely used in the treatment of juvenile idiopathic arthritis patients.